Analisis HES Terhadap Implementasi Pajak Kurang Bayar Yang Terdapat Dalam Pasal 13 Ayat (2) Undang-Undang Nomor 28 Tahun 2007 Tentang Ketentuan Umum Dan Tata Cara Perpajakan - Pratiwi, Anisha Resti; Nurnazli, Nurnazli; Hilal, Syamsul; Faizal, Liky (Fakultas Syariah INSURI Ponorogo, 2023)
The tax collection system in Indonesia to the self-assessment system, Problems that occur, Tax payers, tend to manipulate the calculation of the taxes they pay so that the tax status is nil. The problems of this research are: 1) How is the implementation of article 13 paragraph (2) Law Number 28 of 2007 concerning General Provisions and Tax Procedures at the Tax Service Office in Bandar Lampung City? 2) What is the Analysis of Sharia Economic Law on the Implementation of Article 13 paragraph (2) of Law Number 28 of 2007 Concerning General Provisions and Tax Procedures At the Tax Service Office in Bandar Lampung City? The method used is qualitative. including the type of field research, after reporting the SPT, the checks and if the calculation results are found that are not appropriate, then the status of underpayment, the office will issue an Underpaid Tax Assessment Letter, Then the Taxpayer pays the deficiency, plus a fine of 2% for 24 months. The concluded that implemented properly and according to Islamic law the administrative sanctions given are a form of giving a deterrent effect to obey and correct mistake, as long as there is no injustice then it is permissible.